ANALISIS PELAKSANAAN TRIAS UKS (USAHA KESEHATAN SEKOLAH) DALAM PENYAMPAIAN INFORMASI KESEHATAN REPRODUKSI REMAJA DI SMP AN NIZAM MEDAN TAHUN 2019 - Raudiah Raudiah; Namora Lumongga Lubis; Tengku Moriza (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2020)
Adolescent reproductive health becomes a serious problem. Many adolescents experience unwanted pregnancy to HIV / AIDS. It is hoped that UKS can become a forum to improve students' abilities and skills in shaping healthy behavior. The purpose of the study was to analyze the implementation of UKS in the delivery of information on adolescent reproductive health in Medan AN NIZAM Middle School in 2019. The research method uses mixed methods with a sequential explanatory approach, a population of 164 people, a quantitative sample using a total population while qualitative informants 4 people. Data analysis was performed univariately, bivariate using chi-square, multivariate using multiple logistic regression at a confidence level of 95% (α = 0.05) and depth interview of informants. Quantitative research results show that variables that influence the analysis of the implementation of UKS in the delivery of reproductive health information are knowledge (Pvalue = 0.008) and attitude (Pvalue = 0.001). Qualitative research results show that students have received good reproductive health information but the UKS activities are not going well so that it affects students' attitudes in implementing UKS. It is expected that the active role of the school, teachers, and the entire school community in implementing UKS, as well as cooperation between related parties will be further enhanced so that the implementation of UKS is more optimal Keywords : School Health Business (UKS), Reproductive Health, Knowledge, Attitude, Infrastructure Facilities, Human Resources (HR)